Effect of Lactiplantibacillus plantarum cell-free culture on bacterial pathogens isolated from cystic fibrosis patients: in vitro and in vivo studies - Abán, Carla Luciana; Orosco, Silvia; Argañaraz Aybar, Julio Nicolás; Albarracín, Leonardo; Venecia, Analía; Perret, Liliana; Ortiz Mayor, Sonia; Nishiyama, Keita; Valdéz, Juan Carlos; Kitazawa, Haruki; Villena, Julio; Gobbato, Nadia (Frontiers in Microbiology, 2024)
This study aimed to investigate the effects of the cell-free supernatant of Lactiplantibacillus plantarum ATCC® 10241TM on the biofilm-forming capacity of Pseudomonas aeruginosa strains isolated from cystic fibrosis (CF) patients. In addition, the study evaluated the in vivo potential of the cell-free supernatant to modulate inflammation and reduce lung damage in mice infected with P. aeruginosa strains or co-challenged with P. aeruginosa and the Streptococcus milleri group (SMG). The results showed that CF-derived P. aeruginosa strains can infect the respiratory tract of adult mice, inducing local inflammation and lung damage. The severity of these infections was exacerbated when P. aeruginosa was co-administered with SMG. Notably, nebulization with the cell-free supernatant of L. plantarum produced beneficial effects, reducing respiratory infection severity and inflammatory responses induced by P. aeruginosa, both alone or in combination with SMG. Reduced bacterial loads and lung damage were observed in supernatant-treated mice compared to controls. Although further mechanistic studies are necessary, the results show that the cell-free supernatant of L. plantarum ATCC® 10241TM is an interesting adjuvant alternative to treat P. aeruginosa respiratory infections and superinfections in CF patients.